CONTRIBUTIONS TO EVALUATE THE CURRICULUM IN THE FACULTY OF EDUCATION NATIONAL UNIVERSITY OF SAN MARCOS - Delgado Santa Gadea, Kenneth (2014)
During 2011 it has investigated the application of teaching techniques and assessment in undergraduate and graduate courses. For 2012, we have completed the undergraduate info Base 2008 and incorporated information about the art of observation and analysis of Flanders (as amended), as well as interviews with teachers of Didactic and Educational Evaluation. This was used as input to determine if there are important conditions to effect or sustantive innovations in design and curriculum development, especially in the case of undergraduate studies are already outdated, as they correspond to a proposal in 2003.